Plant growth regulator on micro-sprinkler for mango `Palmer’ floral induction in Brazilian Semiarid - Simões, Welson Lima; Mendes Ferreira, Kalline; Soares da Silva, Jucicléia; Carlos Mesquita, Alessandro; do Carmo Mouco, Maria Aparecida; Gonçalves Torres Junior, Vinicius; Fernandes Barbosa, Kaio Vinicius; Alves Sobral, Yuri Rafael (Comunicata Scientiae, 2023)
Application of the plant growth regulator paclobutrazol (PBZ) to aid mango floral induction has been widely performed by mango producers. However, its application has been done manually, resulting in low uniformity of application and losses with labor. The objective of this study was to adjust the PBZ dose to be applied via micro-sprinkler system for floral induction, indicating an efficient management of ‘Palmer’ mango in the Brazilian semiarid. The experiment was conducted at Saúde Farm, located in Petrolina-PE, Brazil. The experimental design used was randomized blocks, with five doses of PBZ, applied via irrigation system (T1 - 0.56; T2 - 1.12; T3 -1.68; T4 - 2.24; and T5 - 2.80 g a.i. linear m-1 canopy) and a conventionally applied dose (T0 - 2.80 g a.i. linear m-1 of canopy, manually applied broadcast), with four replicates. The variables analyzed were: photosynthesis rate, stomatal conductance, transpiration, leaf temperature, number and length of panicles, number of fruits per plant, average fruit weight, yield, pulp firmness, titratable acidity and total soluble solids in the fruits. At the conventionally applied dose (2.8 g a.i. linear m-1 of canopy), PBZ application via micro-sprinkler irrigation system proved to be the most efficient way to reduce photosynthesis rate, stomatal conductance and transpiration. PBZ applied via micro-sprinkler irrigation system at a dose of 0.56 g a.i. linear m-1 of canopy promotes greater number of panicles and yield in ‘Palmer’ mango.